Minutea Object Extraction in Fingerprint Image Using Morphological Methods and Gabor Filters (Ekstraksi Objek Minutea Pada Citra Sidik Jari Dengan Metode Morfologi dan Gabor Filter) - Julius Santony (Universitas Putra Indonesia YPTK Padang, 2020)
Minutiae is part of the fingerprint, which is the point where the fingerprint line stops or branches, which can be observed by scanning at a resolution of 500 pp. a fingerprint has minutiae that range from 50-100 pieces scattered throughout the surface of the fingerprint. To clarify the fingerprint can be done by extracting the minutiae contained in the fingerprint. With this extraction process, fingerprint images can be clarified, so identification of a fingerprint will be easy to do. This research extracts minutiae objects in the fingerprint image, so that the fingerprint line object can be seen clearly. The first stage in this research is object detection and edge detection using morphological methods. The next step is the extraction of minutiae objects with the gabor filter and minutiae extraction . The results obtained can display the fingerprint line of the fingerprint image clearly. From the results of testing 10 fingerprint images proved that the minutiae object in the image can be extracted, so that the fingerprint line of the image is clearer than the original image.